Pharmacological Management of Gastro-Esophageal Reflux Disease: An Update of the State-of-the-Art - Savarino V; Marabotto E; Zentilin P; Demarzo MG; de Bortoli N; Savarino E (Dove Medical Press, 2021)
Vincenzo Savarino,1 Elisa Marabotto,1 Patrizia Zentilin,1 Maria Giulia Demarzo,1 Nicola de Bortoli,2 Edoardo Savarino3 1Department of Internal Medicine (DIMI), University of Genoa, Genoa, Italy; 2Department of Translational Research and New Technologies in Medicine and Surgery, University of Pisa, Pisa, Italy; 3Department of Surgery, Oncology and Gastroenterology, University of Padova, Padova, ItalyCorrespondence: Vincenzo SavarinoDepartment of Internal Medicine (DIMI), University of Genoa, Genoa, ItalyEmail vsavarin@unige.itAbstract: Gastro-esophageal reflux disease (GERD) is a highly prevalent, chronic disorder, whose knowledge remains limited and the management of these patients changes continuously. This review provides a summary of the most recent advancements in the pathogenesis of this disease and the new drugs introduced into the market to overcome some of the unmet needs of traditional therapies. Nowadays, the most fruitful diagnostic examinations are 24-hour impedance-pH monitoring, which allows us to separate true NERD from esophageal functional disorders and high-resolution manometry, which helps to exclude the existence of motility disorders sharing the same symptoms of GERD. Proton pump inhibitors (PPIs) remain the first-choice therapy in the treatment of GERD, but a consistent proportion of these patients continue to experience symptoms despite their intake. These cases pertain mainly to the subpopulation with non-erosive reflux disease (NERD) and represent very challenging clinical situations, because it is mandatory to understand the reasons for PPI failure. The management of these difficult patients requires necessarily to test them and avoid the use of empiric treatments that are often unsuccessful, costly and potentially dangerous. Recently, several new drugs have been used to increase the defensive properties of this mucosa with promising results in randomized clinical trials.Keywords: medical management of GERD, proton pump inhibitors, potassium competitive acid blockers, PPI-refractory patients, esophageal mucosal resistance, mucosal protective agents, bile acid sequestrant drug